2022
DOI: 10.1021/acs.accounts.2c00044
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Symmetry Breaking Charge Transfer in BODIPY Pairs

Abstract: Metrics & MoreArticle Recommendations * sı Supporting Information CONSPECTUS: Symmetry breaking charge transfer (SBCT) is a process in which a pair of identical chromophores absorb a photon and use its energy to transfer an electron from one chromophore to the other, breaking the symmetry of the chromophore pair. This excited state phenomenon is observed in photosynthetic organisms where it enables efficient formation of separated charges that ultimately catalyze biosynthesis. SBCT has also been proposed as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 57 publications
3
65
0
Order By: Relevance
“…44,45 Hence controlling the conformational exibility and the concomitant manifestation of undesired radiative and non-radiative deactivation pathways of the SB-CS state is vital for a long-lived CS state, thereby enhancing photovoltaic efficiency. 3,46 Core-annulated near-orthogonal arranged perylenediimide dimers have found extensive applications as non-fullerene acceptors in organic solar cells owing to their greater solubility, reduced aggregation and excimer formation. 47,48 Though vital for photovoltaic applications, the excited-state dynamics of heteroatom annulated PDI dimers remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 Hence controlling the conformational exibility and the concomitant manifestation of undesired radiative and non-radiative deactivation pathways of the SB-CS state is vital for a long-lived CS state, thereby enhancing photovoltaic efficiency. 3,46 Core-annulated near-orthogonal arranged perylenediimide dimers have found extensive applications as non-fullerene acceptors in organic solar cells owing to their greater solubility, reduced aggregation and excimer formation. 47,48 Though vital for photovoltaic applications, the excited-state dynamics of heteroatom annulated PDI dimers remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The SB-CS reaction dynamics and the associated solvent effect were well-resolved via femtosecond electronic and vibrational spectroscopy. Dynamic solvent effects were observed in SB-CS reactions for which the dominant contribution to the activation energy comes from the solvent reorganization motions. In such cases, the energy of the CS system is mainly a function of solvent configuration, and hence, the CS reaction is mainly driven by solvent dynamics. Although these studies defined the role of solvent effects on the occurrence of CS, the contribution of intramolecular nuclear motion, especially the low-frequency vibration, to the SB-CS reaction was scarcely studied …”
mentioning
confidence: 99%
“…Bianthryls (BAs) played a key role in the development of photophysics . In particular, 9,9′BA is the prototype for symmetry breaking charge separation (SBCS), a topic which continues to excite wide interest. Lippert, Mataga, and co-workers showed that this symmetrical ( D 2 d ) molecule unexpectedly supports charge transfer type emission in polar solvents. This anomaly was widely investigated, and in an important series of papers Barbara and co-workers showed that the dynamics of CS in 9,9′BA closely follow those of solvation, suggesting a dominant role for solvent orientation dynamics in symmetry breaking and CS state stabilization. , Given the apparently dominant role of the solvent, it seems pertinent to ask whether the initial molecular symmetry plays a role in the CS. To date, there is only one photophysical study of other unsubstituted BAs; here we employ ultrafast transient absorption (TA) and femtosecond stimulated Raman spectroscopy (FSRS) to study excited state structural dynamics in the newly synthesized 1,9′BA, which has both reduced symmetry compared to 9,9′BA ( C s ) and its two anthracene moieties are linked at different carbons, giving them slightly different electronic structures …”
mentioning
confidence: 99%
“…where k B is Boltzmann's constant. Using the a value calculated for the slower relaxation time and assuming ΔΘ to be 27°(from the DFT/TDDFT calculation), we recover the hydrodynamic volume of the rotating particle as 54 Å 3 . This should correspond to the hydrodynamic volume of the rotating body (here the anthracene unit).…”
mentioning
confidence: 99%